BER analysis of FFH/FSK system with self-normalzing receiver over intentional and unintentional interference channels - Toh, Yew Ber. (2008)
In this dissertation, the closed-form bit-error rate (BER) expressions for a uncoded fast frequency-hopped binary frequency-shift keying (FFH/BFSK) system using a non-linear diversity-combining receiver in the presence of multi-tone jamming (MTJ) and additive white Gaussian noise (AWGN) conditions over a non-fading channel are obtained. The main receiver studied is a self-normalizing receiver. A comparison of various receivers is done in later sections. In order to validate the theoretical BER expressions obtained, we compare the analytical BER results of this receiver with the corresponding simulation results. The close match between the two sets of results validates the theoretical BER expression and justifies the use of Taylor-series approximation. Initially, a fix signal-to-noise ratio (SNR) of 13.35 dB is chosen. By mean of a numerical search, we obtain the worst-case number of jamming tone, Q, which results in a worst-case BER performance.